2022
DOI: 10.1093/jac/dkac125
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of azole resistance in clinical and environmental strains of Aspergillus fumigatus in Turkey: a multicentre study

Abstract: Objectives Aspergillus fumigatus causes several diseases in humans and azole resistance in A. fumigatus strains is an important issue. The aim of this multicentre epidemiological study was to investigate the prevalence of azole resistance in clinical and environmental A. fumigatus isolates in Turkey. Methods Twenty-one centres participated in this study from 1 May 2018 to 1 October 2019. One participant from each centre was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Studies showed that triazole‐resistant Aspergillus strains compared to susceptible ones have elevated mortality rates (>20%), despite the application of appropriate antifungal therapy 2,50,51 . Recently, Cao et al, showed that the prevalence rates of A. fumigatus were 45.8%, 64.7% and 62.5% in environmental samples collected in 2014, 2016 and 2018, respectively, which is consistent with their previous reports showing a range of 35% to 77.8% 52–54 .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Studies showed that triazole‐resistant Aspergillus strains compared to susceptible ones have elevated mortality rates (>20%), despite the application of appropriate antifungal therapy 2,50,51 . Recently, Cao et al, showed that the prevalence rates of A. fumigatus were 45.8%, 64.7% and 62.5% in environmental samples collected in 2014, 2016 and 2018, respectively, which is consistent with their previous reports showing a range of 35% to 77.8% 52–54 .…”
Section: Discussionsupporting
confidence: 67%
“…TR34/L98H mutations in the cyp 51A gene were detected in 47.4% of ARA f isolates. However, in 52.6% of phenotypically resistant isolates, no mutations were detected within the cyp 51A gene 51 . Moreover, the prevalence of ARA f in a Danish national surveillance study was 6.1% (66/1083) at patient level and TR 34 /L98H was the most common alteration, but non‐ cyp 51A‐mediated resistance accounted for 19.7% (13/66) 58 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Much of the current research on azole resistance is focused on the expression or modification of the drug target Cyp51 (Bueid et al, 2010 ; Perez-Cantero et al, 2020 ). Recent estimates for azole resistance displayed that more than 50% of the isolations included non-Cyp51 mutants that exhibit azole resistance for unexplained causes (Ener et al, 2022 ). Hence, additional treatment strategies are necessary for azole resistance to the human fungal pathogen A. fumigatus .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on azole resistance caused by Erg11A mutations and high expression of drug pumps in clinical and environmental settings (Bueid et al, 2010;Perez-Cantero et al, 2020). In recent years, an increasing number of A. fumigatus resistant isolates have been identified for having non-cyp51A mutations but with unexplored verification related to drug resistance (Ener et al, 2022). The integrity of mitochondrial function is an important guarantee of multiple cellular processes (Vakifahmetoglu-Norberg et al, 2017;Akbari et al, 2019;Rossi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%